Lignin extractions from oil palm empty fruit bunch under pressurized and inert conditions - Arfat, Md; Mustafa, Abu Hasnat; Madduluri, Venkata Rao; Rasidi, Roslan; Mohd Hasbi, Ab Rahim (International Scientific Organization, 2024)
In this work, lignin was extracted from palm oil empty fruit bunch (EFB) for the first time under pressurized and inert conditions in the presence of deep eutectic solvents (DES). The choline chloride and the oxalic acid were mixed at a ratio of 1:1 to prepare DES, which successfully extracted around 30wt.% of lignin at a relatively mild temperature and pressure. Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (H-NMR) and differential scanning calorimetry (DSC) were used to analyze lignin, whereas X-ray powder diffraction (XRD) was used to investigate the solid residues. FTIR analysis revealed the characteristics of lignin with a major functional group composed of phenolic, aliphatic hydroxyl, and conjugated alkene. The thermal stability of lignin and EFB was confirmed by using DSC. The crystallinity of the solid residue consisting of cellulose was observed to be affected by different temperatures, with the highest value (43.5 %) at 80 oC. The yield of lignin extracted under a pressurized and inert environment shows more than double the value of lignin as compared to the analogue process under atmospheric pressure and also shows comparable lignin yield with microwave-assisted extraction systems. Thus, it provides a new, facile, and efficient approach to the delignification of lignocellulosic biomass.